Safety and tolerability of Ramipril 10 mg in high risk Bangladeshi patients following the criteria of the HOPE study: A multi center open, non comparative study (University Heart Journal, 2009)
Renin angiotensin aldosterone system plays an important role in the pathogenesis of cardiovascular events. ACE inhibitors are known to have a beneficial effect on atherosclerosis progression affecting multiple arterial territories of the body. Several outcome trials utilizing ACE inhibitors have shown reduction of death, NH and stroke in broad range of patients. HOPE study, the landmark trial using Ramipril, has shown beneficial effects in high risk patients using Ramipril 10mg/day in the western population. The aim of the present study was to evaluate the safety and tolerability of Ramipril 10mg/day in Bangladeshi patients. The criteria for recruitment were similar to those of the HOPE study except age (45 years or older were included in the present study). The study showed that this target dose of Ramipril would be reached in Bangladeshi patients, as in the HOPE study, in order to achieve a full therapeutic effect. Lower incidence of adverse events and less distontinuation rate of the drug was encouraging. It is concluded from the study results that Ramipril at a dose of 10mg/day can be used in Bangladeshi patients with reasonable safety and are well tolerated.   doi: 10.3329/uhj.v5i1.3432 University Heart Journal Vol. 5, No. 1, January 2009 3-8